Tax Planning for Corporate Income Tax at PT Lippo General Insurance, Tbk - Nasihah Fauzia; Ida Farida Adi Prawira; Memen Kustiawan (Jurnal Riset Perpajakan: Amnesty, 2024)
The aim of this research is to determine the application of tax planning as an effort to increase the efficiency of Corporate Income Tax Expenses at PT Lippo General Insurance. Descriptive and quantitative research methods are the research methods used in this research and use a case study approach. The results of the research show that PT Lippo General Insurance can still minimize its potential tax payable in 2023 by saving on corporate income tax. Companies can carry out collections with the aim of saving on the company's annual tax rate by calculating the weight of PPh article 21 using the gross up method.